Estudo óptico e estrutural de nanopós de Y3AI5O12 dopados com Eu3+ e Ce3+ sintetizados via processo sol-gel proteico - Santos, Daniel Felix Dias dos (2013)
Optical and structural properties of nanopowders of Y3Al5O12 (YAG), Y3-xEuxAl5O12 (YAG:Eu) and Y3-xCexAl5O12 (YAG:Ce) (x=1 and 2mol%) were studied in the present work. The samples were synthesized via the Proteico Sol-Gel Process. X-ray diffraction showed that YAG single phase could be obtained after calcinations of the xerogels at 950°C/3h or 1050°C/2h. The scanning electron microscopy confirmed that at 950°C/3h the powders are formed by rods with a diameter of about 68 nm and 0.7 ìm in length. For the samples produced at 1050°C/2h two types of morphology were found consisting of needles with a diameter around 44 nm and 0.72 ìm in length, and rounded particles with an average diameter of 130 nm. The Energy-dispersive X-ray spectroscopy confirmed the presence of the dopants and showed that in all nanopowders there were impurities inherited from coconut water. The XANES results confirmed that the dopant ion was incorporated in YAG:Eu nanopowders, as Eu3+ and in the YAG:Ce nanopowders, the dopant was incorporated predominantly as Ce4+ ions. The radioluminescence emission spectra of YAG:Eu and YAG:Ce nanopowders were composed by the typical transitions characteristics of the Eu3+ and Ce3+ ions in the visible region. . Only the YAG:Eu nanopowders showed photoluminescence emission and the reason is that in the case of the Ce-doped YAG most part of the dopant is in its tetravalent charge state that is not optically active.. Nevertheless, the lifetime of the luminescent of the Ce-doped nanopowders were possible to obtain using monochromatic pulsed X-rays and the characteristic lifetime constant is around 48 ns.